2017
DOI: 10.1080/09638237.2017.1340601
|View full text |Cite
|
Sign up to set email alerts
|

The replacement of assertive outreach services by reinforcing local community teams: a replication study reporting comparative outcomes and patient reported experience

Abstract: Results are consistent with earlier studies. Reinforcing community mental health teams can provide an integrated service model that is clinically effective and equally acceptable to patients, making this a viable and affordable alternative to orthodox AO teams.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 18 publications
1
14
0
Order By: Relevance
“…However, further studies replicated a majority of the analysed effects [43] or confirmed previous findings [44,45]. Finally, there were a successful confirmation study from the public health area [46] and a partially successfully economics replication study [47] (Suppl. Table 1).…”
Section: Methodssupporting
confidence: 58%
“…However, further studies replicated a majority of the analysed effects [43] or confirmed previous findings [44,45]. Finally, there were a successful confirmation study from the public health area [46] and a partially successfully economics replication study [47] (Suppl. Table 1).…”
Section: Methodssupporting
confidence: 58%
“…Only two studies included a negative experience. 26,29 For people with complex care needs the experience was generally positive. 27 In Wye et al 35 a coordination centre put a care package in place to support a dying person at home.…”
Section: Coordinated Care Across Teamsmentioning
confidence: 99%
“…A study by Firn et al 30 reporting on a 4-year observational study of 112 patients who were mentally ill without intellectual disability, showed that replacing specialist assertive outreach teams with ‘reinforced’ community mental health teams may maintain patients in crisis out of hospital and is well tolerated by patients. Although at this stage we cannot comment on which model is associated with better clinical and cost outcomes, understanding the provision and aspirations of ISTs for people with intellectual disability and behaviours that challenge will provide useful background to service development and care quality improvements.…”
Section: Discussionmentioning
confidence: 99%